Assessing supplementing strategies for beef cattle in a bale grazing system using grass hay during variable winter conditions - Undi, Michael; Sedivec, Kevin; Bachler, Jessalyn (Frontiers in Animal Science, 2024)
Introduction Beef cattle in the Northern Great Plains of the United States of America are normally kept in open dry lot pens in winter. Practices such as bale grazing, swath grazing, stockpiling, and corn residue grazing, can be used to extend the grazing season and minimize dry lot use. Extending the grazing season has several advantages over dry lot use but arguably the most important benefit is cost savings due to lower labor and input costs. Strategies selected to supplement cattle in extended grazing systems should maintain cost savings while providing required nutrients to cattle. This study was conducted to evaluate supplementing strategies for beef cattle in a bale grazing system using grass hay during variable winter conditions. The study was conducted across variable winter conditions that are encountered in winters in the US Northern Great Plains. Methods The study extended over four years. Each year, non-lactating pregnant beef cows (n = 64, year 1; n = 80, year 2, 3, 4) were divided into eight groups of similar average body weight and randomly assigned to one of four bale grazing treatments as follows: a) bale grazing grass hay, b) bale grazing grass hay treated with a liquid supplement, c) bale grazing grass hay and alfalfa hay, and d) bale grazing grass hay and plus 1.8 kg corn DDGS/head/day. Animal performance was assessed from two-day body weights and body condition scores taken at the start and end of the study. Data analysis considered the fixed effects of treatment, year, and treatment x year interaction. Results Final BW tended (P = 0.09) to be greatest following corn DDGS supplementation and lowest when grass hay was offered. The treatment strategy x year interaction (P = 0.026) for ADG showed that corn DDGS supplementation resulted in positive ADG across the years regardless of environmental conditions. Liquid or alfalfa hay supplementation resulted in positive ADG when environmental conditions were favorable. Final BCS (P = 0.005) and BCS change (P = 0.004) were greater following corn DDGS supplementation, intermediate following alfalfa hay or liquid supplementation and lowest when grass hay was fed. Supplementation costs ranged from $1.33 to $1.90/head/day, the highest cost occurred with corn DDGS supplementation mainly due to cost of corn DDGS and labor required to deliver corn DDGS to cattle on pasture. Discussion Alfalfa hay or molasses-based liquids increased diet CP content but did not supply adequate energy in severely cold winters. Despite relatively higher supplement costs, high energy supplements such as corn DDGS may be required in severely cold winters where cattle require extra energy. Supplement selection should consider supplement effectiveness to meet animal nutrient requirements particularly in adverse winter conditions such as those encountered in the US Northern Great Plains.